CURRENT SITUATION AND PROBLEMS OF “DIGITALIZATION” IN UKRAINE - Dovbysh , Anatolii; Kotukh, Yevhen (Pressing Problems of Public Administration, 2021)
The article examines the features of digitalization in public administration, formulates the main cybersecurity directions. Modern “digital movement” means the introduction in the field of public administration of various methods of digitization, which are characterized by certain innovations by the authorities, the transparency processes inside the authorities, cooperation between last ones and citizens. More and more public organizations need to address important issues of their domestic policy, especially those related to the security of publicly available online data and information, and increasingly organize close cooperation between various officials and employees, as well as with members of the community. Taking into account the complex scientific and methodological analysis, some features of the organization of communication of public administration bodies depending on the level and size of the organization are highlighted. The current situation with cybersecurity is analyzed, as well as ways to increase its level in the field of public administration in Ukraine. It is proved that the level of digitalization and informatization, and, accordingly, the development of e-government is low. The reasons for this are: – unsatisfactory material and technical support of public administration bodies, in particular, obsolescence of computer and organizational equipment; – lack of high-speed Internet, especially in small towns, villages and hamlets; – insufficient level of knowledge, skills and abilities most in demand in the field of electronic document management technologies and secure online communication technologies, due to the low level of awareness of cybersecurity modern means. The priority ways to increase the level of cybersecurity in the public sector in modern circumstances should be increasing budget funding in the relevant field, strategic investment in cyber analytics and cloud technologies, the creation of special units for cybersecurity, installation of modern software and its permanent updating, regular training of all employees in the field of organizational and personal information protection of.